Watershed 89 : the future for water quality in Europe : proceedings of the IAWPRC Conference, held in Guildford, U.K., 17-20 April 1989 - Wheeler, D.; Richardson, Mervyn; Bridges, J. (Advances in water pollution control., 1989)
Watershed 89: The Future for Water Quality in Europe, Volume 1 contains the proceedings of the International Association on Water Pollution Research and Control Conference on the Future for Water Quality in Europe, held in Guildford, UK, on April 17-20, 1989. The symposium provided a forum for assessing future prospects for resolving water quality issues in Europe. Topics covered range from contamination of drinking water to the quality of recreational waters and toxicological aspects of pesticides in natural waters.